La mort au cœur de l’histoire des « Sept Maisons » de l’Ouest Gurāgē - Arnaud Kruczynski (Afriques)
The processes of bereavement and funerals are described while raising questions about death in the culture of the western Gurage “Seven Houses”. This description sheds light on the moving relations between different segments of this society. Conceptions about death play a decisive role in the formation of lineages, clans, households and the Seven Houses; they legitimate this social organization in religious terms. Death has been a key theme in the history of western Gurage peoples during the 19th and 20th centuries. It can be seen as a driving force in the emergence and development of the Seven Houses.